IMPLEMENTASI KEBIJAKAN BATAS USIA TERENDAH PENGEMUDI SEPEDA MOTOR DI KOTA SEMARANG - Agasetyo Manuhoro; Hartuti Purnaweni; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Motorcycles are personal transportation which most widely used by the Indonesian people especially in Semarang City. The driver of the motorcycle is often less concerned about the drive regulations up the road. Terms of driving a motorcycles with a minimum age limit of 17 years is still frequently violated regulations by drivers especially students. Many parents, schools and other elements being apathetic and less concerned about this issue. The traffic officers as law enforcement officers also seem sluggish and less resolute in cracking. The aim of this research is to find out how the implementation of lowest age limit’s policy for motorcycle drivers in Semarang by using the phenomenon of the effectiveness of implementation are: policy accuracy, executor accuracy, targets accuracy, and environment accuracy. And to know the supporting factors and obstacles with construct a theoretical model of implementation of the George C. Edwards, Van Meter - Van Horn and Shabbir Cheema - Dennis R. Rondinelli are: communication factor, resources and environment. This research used a qualitative research method descriptive type. The result from this research is the implementation of lowest age limit’s policy for motorcycle drivers in Semarang City has not yet effective. It is seen from the phenomenon of the effectiveness of implementation has not been able to achieve. Then there are factors that hinder so that need for increasing the number of traffic police, budget, infrastructure, enforcement of strict sanctions for traffic police who abuse their authority and learning for people who apathy.